Myers-Briggs typology from the perspective of classification of natural specializations - Ishkov, Aleksandr (Edelweiss Applied Science and Technology, 2025)
The article is devoted to a comparative analysis of the Myers-Briggs Typology (MBTI), based on psychological characteristics of personality, and the classification of natural specializations (CNS), based on neurophysiological features of the nervous system. The purpose of the study is to identify overlaps, differences, and possible ways of integration and development of these two concepts. On the basis of structural analysis, it was found that the dichotomy “extraversion/introversion” of MBTI corresponds to the dichotomy “concrete/abstract” of CNS. The main functions of MBTI (“sensing,” “intuition,” “thinking,” “feeling”) correspond with the classical specializations of CNS: Searcher, Analyst, Synthetic, and Realizator, respectively. The correlation of sixteen MBTI types with sixteen integral specializations of the CNS was established, which demonstrates the neurophysiological basis of each MBTI type, opening the way to a more objective diagnosis of the types through the methods of neurophysiology. The system comparison of MBTI and CNS demonstrates their structural similarity at different levels of content - psychological and biological. This allows us to consider the MBTI as a private, psychological level of the broader neurophysiological model of the CNS. MBTI and CNS, despite their different approaches and methodologies, describe the same underlying individual differences in humans.